Surface roughness assessment with fluoride varnish application: An in vitro study - Apriani, Anie; Naliani, Silvia; Djuanda, Rudy; Teanindar, Shania Hysan; Florenthe, Jessica Quiteria; Baharudin, Ferri (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2023)
Background: The cause of cavities is initially due to roughness on the tooth surface, requiring fluoride varnish to prevent caries, as the varnish applies a fluoride compound to the tooth surface. Fluoride varnish reacts with the tooth enamel surface to form calcium fluoride and fluorapatite, thus making the enamel surface more resistant to demineralization and damage. Purpose: This study aims to compare the roughness of tooth enamel surfaces among three fluoride varnishes under acidic conditions. Methods: The research method uses three fluoride varnish materials: sodium fluoride 5% + tricalcium phosphate, calcium fluoride, and sodium fluoride 5% + casein phosphopeptide-amorphous calcium phosphate 2%. Samples of 81 teeth were divided into three groups (Group 1 without fluoride varnish application, Group 2 application of fluoride varnish with pH 3, and Group 3 application of fluoride varnish with pH 5). The teeth were tested before and after application of the varnishes using the scanning electron microscope and surface roughness tests. Results: The results showed a significant difference in the mean surface roughness of the enamel of the anterior deciduous teeth tested with fluoride varnish. The before and after comparisons in the pH 3 and pH 5 groups were very significant (p-value 0.000). The comparison results in each pH group after fluoride varnish administration showed no significant difference (pH 3 p-value 0.074 and pH 5 p-value 0.196). The tooth surfaces appear to be rougher after administration of an all-acid solution. Conclusion: There is a difference in surface roughness of primary teeth after being given fluoride varnish in low pH 3 immersion for 24 hours.